2020
DOI: 10.1186/s13287-020-01881-7
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α overexpression in mesenchymal stem cell-derived exosomes mediates cardioprotection in myocardial infarction by enhanced angiogenesis

Abstract: Background: Myocardial infarction (MI) is a severe disease that often associated with dysfunction of angiogenesis. Cell-based therapies for MI using mesenchymal stem cell (MSC)-derived exosomes have been well studied due to their strong proangiogenic effect. Genetic modification is one of the most common methods to enhance exosome therapy. This study investigated the proangiogenic and cardioprotective effect of exosomes derived from hypoxiainducible factor 1-alpha (HIF-1α)-modified MSCs. Methods: Lentivirus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 39 publications
7
103
0
Order By: Relevance
“…Current studies reported that HIF-1α directly regulates the expression of genes involved in angiogenesis (42,(50)(51)(52), which including VEGF, platelet-derived growth factor (PDGF), and angiopoietin 1 (Ang-1) (53). The research demonstrated HIF-1αoverexpressed exosomes had a cardioprotective effect on MI rat via enhanced angiogenesis and reduced fibrosis, there were promotional effects on proliferation, migration, and tube forming ability on HUVECs (54). Evidence has elucidated that HIF-1α regulated the expression of VEGF at the transcription level (55).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies reported that HIF-1α directly regulates the expression of genes involved in angiogenesis (42,(50)(51)(52), which including VEGF, platelet-derived growth factor (PDGF), and angiopoietin 1 (Ang-1) (53). The research demonstrated HIF-1αoverexpressed exosomes had a cardioprotective effect on MI rat via enhanced angiogenesis and reduced fibrosis, there were promotional effects on proliferation, migration, and tube forming ability on HUVECs (54). Evidence has elucidated that HIF-1α regulated the expression of VEGF at the transcription level (55).…”
Section: Discussionmentioning
confidence: 99%
“…The speci c development approaches of the exosomes included surface engineering, genetic engineering, chemical modi cation, and membrane fusion [32][33][34]. Of which the genetic engineering generated overexpression of a speci c protein or micro-RNA and exhibited satisfactory outcome: Chen et al found that the GDNF-modi ed human ADSCs-derived exosomes ameliorated peritubular capillary loss in tubulointerstitial brosis [35]; Sun et al revealed that the exosomes derived from the HIF-1α overexpressed mesenchymal stem cells (MSCs) enhanced the angiogenesis to provide cardioprotection in myocardial infarction [36]; and Wang et al discovered that exosomes derived from miR-155-5poverexpressing synovial MSCs enhanced the bio functions of chondrocytes to prevent osteoarthritis [37].…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs were cultured in DMEM supplemented with 10% FBS in a humidified atmosphere containing 5% CO 2 at 37°C. A total of 1 × 10 4 HUVECs were added to each Transwell (Corning, 3422) upper chamber, and 600 μl of fresh medium or culture supernatant containing 10% FBS was placed in the lower chamber [ 29 ]. HUVECs were treated with supernatant from 2D-ADSCs, 3D-ADSCs- or 3D-ADSCs/NO for 24 h, and the group without supernatant was the control group.…”
Section: Methodsmentioning
confidence: 99%